Environmental Literacy Investigation Biology Education Students at Islamic Colleges Based on Gender and Parents' Occupation in Jambi Province - Zb, Aminah Aminah; Harisah, Harisah; Iskandar, Iskandar; Sulman, Fauzan Fauzan (PALASTREN: Jurnal Studi Gender, 2022)
Eivironmental literacy is an important aspect of individual abilities in maintaining environmental conditions. This study aimed to determine the understanding of environmental literacy of Biology Tadris students with Islamic religious college backgrounds based on Gender and Parents’ Occupation. This study uses a descriptive quantitative approach. The research population is Biology Education students from Islamic Religious College in Jambi Province. The research sample was determined by purposive sampling, which consisted of 118 people. The study results are; students’ environmental literacy in general is quite good which female students are in good criteria with slightly better than boys. Then in terms of the work of parents, the criteria of good enough which the highest average score was obtained by farmers. Environmental knowledge and student cognitive skills obtained from learning and information obtained from the environment. The ability of environmental literacy based on gender has become a must to be observed as a form of consistency and seriousness in understanding the differences and the need to increase the understanding of environmental literacy that students own.